2019
DOI: 10.1016/j.bodyim.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of interventions aiming to promote positive body image in adults: A systematic review

Abstract: Highlights  Positive body image interventions improve aspects of health and well-being.  Fifteen studies, evaluating 13 interventions, were eligible for inclusion.  The two interventions for men, rated as weak, did not improve positive body image.  Strong and moderate quality interventions improved positive body image in women.  Future interventions should target multiple components of positive body image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 79 publications
(283 reference statements)
4
53
0
2
Order By: Relevance
“…As part of the research agenda on nature exposure and psychological well-being, some scholars have focused specifically on the construct of positive body image, which refers to an "overarching love and respect for the body" that includes appreciation of the body and its functions, acceptance of the body despite its imperfections, and body-protective behaviours (Tylka, 2018, p. 9). This focus is warranted not only because promoting healthier body image is important in its own right (Guest et al, 2019;Tylka & Piran, 2019), but also because of the range of benefits that are related to positive body image. Such benefits include more positive emotional and eudaimonic well-being (e.g., Davis, Fowler, Best, & Both, 2019;Swami, Weis, Barron, & Furnham, 2018), positive self-care health behaviours (e.g., Andrew, Tiggemann, & Clark, 2016;Gillen, 2015), and adaptive eating styles that are associated with lower body mass indices and weight stability (e.g., Tylka, Calogero, & Daníelsdóttir, 2015;Tylka, Calogero, & Daníelsdóttir, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As part of the research agenda on nature exposure and psychological well-being, some scholars have focused specifically on the construct of positive body image, which refers to an "overarching love and respect for the body" that includes appreciation of the body and its functions, acceptance of the body despite its imperfections, and body-protective behaviours (Tylka, 2018, p. 9). This focus is warranted not only because promoting healthier body image is important in its own right (Guest et al, 2019;Tylka & Piran, 2019), but also because of the range of benefits that are related to positive body image. Such benefits include more positive emotional and eudaimonic well-being (e.g., Davis, Fowler, Best, & Both, 2019;Swami, Weis, Barron, & Furnham, 2018), positive self-care health behaviours (e.g., Andrew, Tiggemann, & Clark, 2016;Gillen, 2015), and adaptive eating styles that are associated with lower body mass indices and weight stability (e.g., Tylka, Calogero, & Daníelsdóttir, 2015;Tylka, Calogero, & Daníelsdóttir, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding protective factors for ED symptoms, Jankowski et al (2017) assessed the impact of a DB intervention on male body appreciation and found non‐significant effects. However, systematic reviews have noted that body appreciation is a key protective factor for the development of body dissatisfaction, and ED and MD symptoms (Guest et al, 2019; He, Sun, Zickgraf, Lin, & Fan, 2020), suggesting further investigation of this variable is warranted. Jankowski et al's (2017) results may be related to the omission of some of the activities, shortening the protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Jankowski et al's (2017) results may be related to the omission of some of the activities, shortening the protocol. Thus, understanding how other DB interventions designed for men impact protective factors for ED and MD symptoms may be a promising research avenue (Guest et al, 2019; He et al, 2020). Therefore, future studies may benefit from measuring body appreciation, since it may be a protective factor for body dissatisfaction, ED, and MD symptoms (He et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Interventions that emphasize eating intuitively have improved body esteem and psychological health and have stabilized weight. 12,13 Intuitive eating consists of 10 core principles that revolve around physical and emotional awareness, as well as making peace with food and the body. 14 The concepts of intuitive eating were initially developed to treat chronic dieters.…”
Section: Intuitive Eatingmentioning
confidence: 99%